Reestructuración técnico comercial en la empresa Rodar Carga S.A.S. (2020)
Initially, an initial diagnosis was made to the company, to identify its current status and the different factors that directly impact it; An analysis was applied with the tool proposed by the Chamber of Commerce of Bogotá to detail key aspects of the company. Following this, a market study was carried out, which helped determine relevant aspects for the correct commercialization of the service offered by the company, this was achieved through the analysis of the sector, the identification of entry barriers, the segment was segmented market, customers using this service were identified to which a survey was applied, the demand forecast was made and the market plan was made. Then, the technical study was carried out, with which all the elements that directly impact the service were established, such as capacities, labor, office equipment, space distribution, good ergonomics and anthropometry practices, safety elements and health at work and the 5's in addition to the environmental impact. In addition, the mobile design and implementation was proposed in order to reduce internal activities and better control the logistics process of the company. Finally, a financial summary of the organization was made, where the viability of the project was demonstrated, through accounting elements such as the income statement and the company's balance sheet.